IMPLEMENTASI SISTEM MANAJEMEN MUTU (ISO) 9001 : 2008 DAN KEPEMIMPINANTERHADAP PENINGKATAN KINERJA GURU DI SMK NEGERI 1 JOMBANG - Nur Maksum (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
SMK Negeri 1 Jombang is one country-level vocational education institutions in the region Jombang already received ISO. So that in the school there are many changes to the system are changed to the better for the progress of the school. The problems of this study: (1) Is the implementation of ISO 9001-2008 Quality Management System Performance Improvement Against Influential Teacher at SMK Negeri 1 Jombang, (2) Is Against Influential Leadership Performance Improvement Teacher at SMK Negeri 1 Jombang. (3) What is the most dominant variables that affect the quality management system ISO 9001-2008 and leadership Against Performance Improvement Teacher at SMK Negeri 1 Jombang. This study will be conducted Nengeri Vocational High School (SMK) I Jombang, which address at Jl. Dr. Sutomo No. 15, Jombang, East Java Phone: (0321) 861516. The number of samples taken as many as 50 respondents. The variables in this study independent variables (X1) in this study is the implementation of a Quality Management System (ISO) 9001: 2008 At SMK Negeri 1 Jombang, independent variable (X2) in this study is the leadership and the dependent variable in this study were (Y) that is Teacher performance. The results of this study, there is a simultaneous effect between variables Implementation of Quality Management System (ISO) 9001: 2008 (X1) and the leadership variable (X2) to variable Teacher Performance in SMK 1 Jombang (Y). as evidenced from the correlation value (R) of 0.965 and Fhitung 313.967 with probability (sig) of 0.000 <0.05. Then the results of testing with multiple regression between variables (X1) and variable (X2) which has the most dominant influence to variable Y is the implementation of a Quality Management System (ISO) 9001: 2008 (X1) with a regression coefficient of 1.169. It is because, the teachers felt that the implementation of the Quality Management System (ISO) 9001: 2008 (X1) to get additional education, knowledge and insights in a systematic and routine.